Are vancomycin dosing guidelines followed? A mixed methods study of vancomycin prescribing practices. Issue 11 (14th April 2021) - Carland, Jane E.; Stocker, Sophie L.; Baysari, Melissa T.; Li, Crystal; Själin, Jacqueline; Moran, Maria A.; Tang, Sarah; Sandaradura, Indy; Elhage, Tania; Gilbey, Timothy; Williams, Kenneth M.; Marriott, Deborah J. E.; et al.
Abstract : Aims: Despite the availability of international consensus guidelines, vancomycin dosing and therapeutic drug monitoring (TDM) remain suboptimal. This study aimed to assess concordance of vancomycin dosing and TDM with institutional guidelines and to identify factors taken into consideration by clinicians when prescribing vancomycin. Methods: A retrospective audit of 163 patients receiving vancomycin therapy (≥48 hours) was undertaken. Data collected included patient characteristics, dosing history and plasma vancomycin and creatinine concentrations. Concordance of dosing and TDM with institutional guidelines was evaluated. Semi‐structured interviews, including simulated prescribing scenarios, were undertaken with prescribers ( n  = 17) and transcripts analysed. Results: Plasma vancomycin concentrations ( n  = 1043) were collected during 179 courses of therapy. Only 24% of courses commenced with a loading dose with 72% lower than recommended. The initial maintenance dose was concordant in 42% of courses with 34% lower than recommended. Only 14% of TDM samples were trough vancomycin concentrations. Dose was not adjusted for 60% (21/35) of subtherapeutic and 43% (18/42) of supratherapeutic trough vancomycin concentrations, respectively. Interview participants reported that patient characteristics (including renal function), vancomycin concentrations, guidelines and expert advice influenced vancomycin prescribing decisions. Despite referring to guidelines when completing simulated prescribing scenarios, only 37% of prescribing decisions aligned with guideline recommendations. Conclusion: Poor compliance with institutional vancomycin guidelines was observed, despite prescriber awareness of available guidelines. Multifaceted strategies to support prescriber decision‐making are required to improve vancomycin dosing and monitoring.